Effect of edible mushroom (Pleurotus ostreatus) on type-2 diabetics (Ibrahim Medical College Journal, 2015)
The prevalence of non-communicable diseases (NCD) like diabetes, hypertension, dyslipidemia and atherosclerotic cardiovascular diseases (CVD) are on the increase globally and predominantly in the South East Asian Region (SEAR). The increasing NCD and its complications burdened the health cost of Bangladesh. The available literatures suggest that edible mushrooms are effective in controlling metabolic risks like hyperglycemia and hypercholesterolemia.The study addressed the metabolic effects of edible oyster mushroom (Pleurotus ostreatus) in diabetic individuals and to assess the undesirable effects of mushroom.A total of 5000 newly registered diabetic women were screened for eligible participants (urban housewives, age 30 50y, BMI 22 27, FBG 8 12 mmol/l; free from complications or systemic illnesses and agreed to adhere to the study for 360 days). The investigations included weight and height for BMI, waist- and hip-girth for WHR, BP, FBG, 2ABF, T-chol, TG, HDL, LDL, ALT and Creatinine starting from the day 0 (baseline) and each subsequent follow-up days: 60, 120, 180, 240, 300 and 360 for comparison between placebo and mushroom groups and also within group (baseline vs. follow up days), individually for placebo and mushroom. The daily intake of mushroom was 200g for the mushroom group and an equivalent calorie of vegetables for the placebo group.Overall, 73 diabetic housewives (mushroom / placebo = 43 /30) volunteered. The mean (with SEM) values of BMI, WHR, BP, FBG, 2ABF, T-chol, TG, HDL, LDL, ALT and Creatinine of the placebo group were compared with the mushroom group. Compared with the placebo, the mushroom group showed significant reductions of FBG (p